STUDY ON EFFECTS OF ENVIRONMENTAL FACTORS TO PLANTS AT BA VI NATIONAL PARK - Minh Quang, Nguyen; Viet Quag, Do; Khanh Toan, Nguyen; Van Sam, Hoang (Journal of Forestry Science and Technology, 2016)
The environmental factors (temperature, humidity, precipitation, soil type, elevation,...) have positive impact to the change of forest ecology in general and National Parks of Vietnam in particular. In the case of Ba Vi National Park, elevation is one of factors which have significant effects to plant diversity. This paper provides information about effect of elevation on plant diversity in Ba Vi National Park which has 3 types of natural forest and 2 types of artificial one. Plant composition is different among the elevation of Ba Vi National Park not only by number of plant species in general but also about high conservation value species. The number of plant species increased by elevation with the highest at 1000 m and the lowest at 400 m above sea level is 156 and 98 species, respectively. The number of plant families also increases by higher elevation. The result also showed that from 400 m up to 1000 m, the higher elevation the more plant biodiversity. The plant species similarity is the highest between 1000 m and 800 m with 40% species appear on both elevation and the lowest between 1000 m and 400 m with only 11% species distributed in both areas.